Solar tracker using Arduino microcontroller and light dependent resistor - Chenchireddy, Kalagotla; Mulla, Gouse Basha; Jagan, Vadthya; Sultana, Waseem; Sydu, Shabbier Ahmed; Giddalur, Eswaraiah (Institute of Advanced Engineering and Science, 2025)
This paper presents a dual-axis solar tracker using Arduino and LDRs. The aim of the proposed paper is to enhance the competence of solar energy harvesting by developing an intelligent solar tracking system. This system employs light-dependent resistors (LDRs) as sensors to detect ambient light levels, enabling precise adjustments of solar panels along both azimuth and elevation axes. The Arduino microcontroller serves as the intellect of the system, orchestrating the synchronized movement of dual-axis servo motors to align solar panels optimally with the sun's point during the day. The core functionality of the solar tracker involves real-time monitoring of LDR readings to calculate the solar azimuth and elevation angles. These angles are then used to situation the solar panels dynamically, ensuring they are constantly oriented near the sun for maximum energy absorption. The implementation of the dual-axis solar tracker using Arduino and LDRs offers several advantages, including increased energy output, better system efficiency, and a reduction in dependency on fixed solar installations. The low-cost and adaptable nature of the proposed system makes it suitable for various applications, such as residential solar installations, off-grid power systems.